The Complexity of The Illegal Fishing Regime in Southeast Asia Case Study: Illegal Lobster Seed Fishing in ASEAN - Lucitania Rizky; Pramestia Sekar Salsabilla; Maulida Tri Utari; Muhammad Najeri Syahrin; Andi Tenri Sompa (Asean Study Center Lambung Mangkurat University, 2021)
Southeast Asia's geographical conditions are an area that has a marine ecosystem most diverse in the world. However, there is an increase in the exploitation and practice of Illegal, Unregulated and Unreported (IUU) fishing which is considered troubling and detrimental to the affected region. This study attempts to analyze the regimes' complexity in illegal fishing in Southeast Asia. The research method used a qualitative approach. Primary data we collect documents and official statements issued by the Asia-Pacific Fishery Commission, ASEAN-SEAFDEC organization, FAO, and policy of ASEAN countries through the ministry of maritime and fisheries. Analysis of the complexity of the three main regimes in IUU complemented by a discussion of these regimes' agendas and similarity policies (overlapping regimes). In dealing with this, countries in the Southeast Asian region are implementing a strategy to keep up with agreed international norms. It has found that 60% of ASEAN member countries adopt the Regional Plan of Action (RPOA). They were shifting the existence of profit-oriented thinking into sustainability-oriented. The regime's complexity illustrates the tumult of an international issue and the whip to increase the country's contribution to the sustainability of a more balanced life by internalizing the international regime's norms.